Pendampingan Pengelolaan Keuangan dan Manajemen Usaha pada Bisnis Albania Coffe & Resto - Fanniya Dyah Prameswari; Mona Tiorina Manurung; Galih Panjalu Pramono; Erika Desyyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Knowledge related to finance and management in running a business is very important. This is the basis for managing a business so that it can survive in an era of developments and increasing business competition. Culinary businesses, such as Albania Coffee & Resto, often face challenges in managing finances and running operations. The purpose of this activity is to provide financial and business management assistance to the Albania Coffee & Resto business located in the Limbangan-Boja area, Kendal Regency, Central Java. This community service provides a real contribution in increasing the capacity of micro, small, and medium enterprises (MSMEs) in the culinary field. By equipping the owners of Albania Coffee & Resto with the knowledge and skills needed, it is hoped that they can increase the competitiveness of their businesses and contribute to local economic growth.